Concept of Apatarpana: Bird’s Eye View (AYUSHDHARA, 2023)
Ayurveda has universal and person-centric approach in relation to health and diseases, which requires essential consideration of several factors in the process of diagnostic work-up. Guidelines regarding Ahara-vihara, Nidra and Brahmcharya are elaborately described in different Ayurvedic compendium in scientific way. One needs to follow these principles or guidelines to achieve Purushartha, namely Dharma (doing activities based on morality), Artha (economic prosperity), Kama (desire), and Moksha (self-realization/liberation). For the maintenance of homeostasis in the body (Dhatusamya) one must follow the instructions regarding daily and seasonal regimens (Dinaharya, Ratricharya and Ritucharya) and treatment modalities of respective diseases. Treatment procedure also depends on individual’s Prakriti, Desha, Kala, Matra etc. According to Ayurveda all treatment modalities can be divided in two folds i.e., Santarpana and Apatarpana. Apatarpana in terms of malnutrition is responsible for developing of several kinds of Kuposana-janya-vyadhi or diseases. Agni vaisamya is prime factors for genesis of all diseases as well as Kuposan janya-vyadhi. Based on severity and etiology they are different in type such as Karshya, Phakka, etc. In India 40% of world’s malnourished children and 35% of developing worlds low-birth weight infants are present. Hence, Agni dipana and proper nutrition plays a very crucial role to solve all major problems related to Apatarpana. In the first step, if we treat the Agnidusti and provide proper nutrition, then breaks the vicious chain of pathogenesis of all Apatarpanaja vyadhis. The study of Apatarpana is very much important in the field of Chikitsa to maintain the quality life.